Money matters for teens workbook : age 15-18 edition - Burkett, Larry; Temple, Todd
Summary: Gives helpful forms and information to teach [teenagers] how to stay out of debt, how to save for a car, college, your own business and how to give money that will make a difference in the world and more. Written from a Christian perspective.